The effects of labor income risk heterogeneity on the marginal propensity to consume - Ettore Savoia (European Central Bank (ECB), 2023)
Using detailed micro-data, this paper documents that households with lower income risk (and higher income levels) exhibit a higher Marginal Propensity to Consume (MPC) in response to transitory income shocks, all else being equal. This finding is particularly significant among unconstrained households and supported by models with precautionary saving only if designed to account for the empirically observed negative correlation between income levels and income risk. This interaction generates saving dynamics such that the stationary distribution of wealth among households facing different risk levels is not polarized. Therefore, it is possible to compare their respective MPCs within wealth and identify the reduction in MPC due to labor income risk. Otherwise, the effects of income risk are masked by wealth effects. In neither case, the MPC depends on (permanent, persistent, or current) income levels, whose direct effect on the MPC is always ambiguous. Finally, simulations of targeted fiscal rebates for specific labor categories reveal that governments cannot simultaneously stimulate aggregate demand and mitigate income risk.
Keywords: D12; D52; D81; E21; J31; 330; Marginal Propensity to Consume; Income Risk; Precautionary Saving